Influencia del tiempo de cocción en las características fisicoquímicas de la chicha de jora - Briceño Prado, Karol Elizabeth (2014)
The present study was aimed to "determine the physicochemical characteristics of chicha, to different cooking times." Zea mays was used previously dried and grinded, 48 suspensions were prepared in water at a concentration of 10% w/v, they were classified into 6 groups each one 8 samples; was cooked each group for 2 hours, 4 hours, 6 hours, 8 hours, 10 hours and 12 hours. Finished cooking, proceeded to refine each of the samples and the filtrate was received in a container of suitable capacity. Inoculated, Saccharomyces cerevisiae culture; the filtrate obtained, the system was adapted respective breathing. He was allowed to ferment for 2 days and the physicochemical analysis to determine organoleptic characteristics, alcohol content, dry matter, moisture, specific weight, reducing sugars, total acidity, volatile acidity, pH, refractive index and Brix was performed. Analyses of chicha after fermentation at different cooking times reported variation in the organoleptic characteristics, progressive increase: reducing sugar content, dry matter content, specific gravity, Brix and total acidity. Unlike the gradual decline in the values of refractive index and volatile acidity. In addition, the cooking time doesn’t influence the determination of pH and alcohol content. Concluded that the physicochemical characteristics of the chicha vary cooking time. Keywords: